Antimicrobial Susceptibility and Occurrence of Resistance genes among Salmonella arizonae isolated from Chicken Meat samples in Sokoto Metropolis, Sokoto State, Nigeria - Garba M.K.; Olonitola, O.S.; Yakubu, S.E.; Abdullahi, I.O. (UMYU Journal of Microbiology Research)
This study was conducted to determine the antimicrobial susceptibility and occurrence of resistance genes among Salmonella Arizonae isolated from chicken meat samples collected in Sokoto metropolis, Sokoto State Nigeria. A total of 400 Chicken’s Meat samples (breast muscle) were collected and examined for the presence of Salmonella organisms. The isolated Salmonella Arizonae were then tested for antimicrobial susceptibility using disc diffusion technique and antimicrobial resistant isolates were then examined for the presence of ampicillin resistance gene blaTEM, chloramphenicol resistance gene floR and tetracycline resistance gene tetA by PCR. Salmonella aizonae were isolated in only 4.5% (18 / 400) of the samples examined. Antimicrobial susceptibility test of the isolates showed susceptibility to nitrofurantoin (94.4%), nalidixic acd (94.4%), oflxacin (77.8%), augmentin (72.2%) and cotrimoxazole (66.7%). However, the isolates were resistant to tetracycline (88.9%), ampicillin (72.2%) and chloramphenicol (66.6%). Only 8 of these isolates were resistant to one or more of the antimicrobial agents tested. Resistance gene analysis of the resistant isolates shows the presence of ampicillin resistance gene, blaTEM in 75% (6 / 8) of the tested isolates. Presence of chloramphenicol resistance gene, floR was also detected in 37.5% (3 / 8) of the isolates. Presence of multiple resistance genes was also detected in the isolates. A combination of two different resistance genes was detected in 62.5% (5 / 8) of the isolates and presence of all the three resistance genes (blaTEM, tetA and floR) was detected in one of the isolates. Antibiotics have been used widely in poultry to treat, prevent infections and also in feeds to promote growth. Such practice has improved poultry performance effectively and economically but has resulted in the increase in the spread of resistant bacterial strains. In our study, a high resistance profile of 88.9% to tetracycline, a popularly use drug in poultry industry and the presence of multiple resistance genes in 62.5% of the isolates was also observed. There is therefore the need for more rational use of antibiotics in animal production and more prudent use in humans.